Development, validation and evaluation of a patient information booklet for rectal cancer survivors with a stoma: A three-step approach. Issue 9 (September 2021) - Giannopoulos, Panagiotis; Mertens, Yannick J.; Secomandi, Laura E.; Olsder, Linde; van Leeuwen, Barbara L.
Highlights: Lack of information to cancer survivors hampers quality of life. Written information should be provided at the healthcare facility. Three-step approach for development of written patient information material. Written material led to high patient satisfaction and increased perceived knowledge. The application of this three-step approach may improve cancer survivorship care. Abstract: Objective: Quantitatively measure the degree of patient satisfaction and perceived acquired knowledge through the development of a patient information booklet for rectal cancer survivors with a stoma, according to a novel three-step approach. Methods: The study included a systematic literature review to identify relevant information for the booklet, which was validated by experts based on relevance, clarity and essentiality. It underwent testing on quality, readability, and layout and design and was quantitatively evaluated by rectal cancer survivors with a stoma. Results: In total, 145 articles were used for the development of the booklet. It scored 91% for relevance according to 17 experts, 70% for readability, 75.63% for quality and 23 out of 32 for design. The mean score of patient satisfaction was 8.03 out of 10. All 20 patients found the booklet 'useful' and 95% felt better informed. Conclusions: The booklet scored high for patient satisfaction and increased perceived acquired information. It ensured satisfactory levels of quality, readability, and layout and design. Practice implications: This study offers a novel three-step approach for development of informational tools for cancer survivors, assuring that a variety of newly created written patient materials would be of increased quality and relevance to any target population.